2018
DOI: 10.3138/ptc.2017-01.ep
|View full text |Cite
|
Sign up to set email alerts
|

“A Learned Soul to Guide Me”: The Voices of Those Living with Kidney Disease Inform Physical Activity Programming

Abstract: Purpose: The purpose of this study was to (a) confirm the barriers to and facilitators of physical activity (PA) among persons living with chronic kidney disease (CKD) in Ontario and (b) inform the design of a Kidney Foundation of Canada Active Living for Life programme for persons living with CKD. Method: Adults living with CKD in Ontario were invited to participate in a cross-sectional survey investigating opinions about and needs for PA programming. The 32-item survey contained four sections: programme deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…Health care professionals, friends and family, and peer support were reported to be influential for encouraging exercise . However, the current lack of an “exercise culture” for dialysis patients was a reported barrier .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Health care professionals, friends and family, and peer support were reported to be influential for encouraging exercise . However, the current lack of an “exercise culture” for dialysis patients was a reported barrier .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported how patients perceived exercise counseling as part of the nurses’ role, but others reported patient concerns over staff workload and how patients were keen to not be perceived as a bother to staff . However, having a trusting relationship with their doctor, and doctor approval for exercise was as a facilitator for exercise engagement, as was peer support and seeing others exercise . Exercise was perceived as a way to develop camaraderie and positive common identities with others .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations